Magmatic processes at the volcanic front of Central Mexican volcanic belt: Sierra de Chichinautzin volcanic field (Mexico) - Velasco Tapia, Fernando; Verma, Surendra P. (Fuat Yavuz - Istambul Technical University, 2013)
The Sierra de Chichinautzin (SCN) volcanic field is considered one of the key areas to understand the complex petrogenetic processes at the volcanic front of the Mexican Volcanic Belt (MVB). New as well as published major- and trace-element and Sr and Nd isotopic data are used to constrain the magma generation and evolution processes in the SCN. From inverse and direct modelling, combined 87Sr/86Sr and 143Nd/144Nd data, and use of multi-dimensional log-ratio discriminant function based diagrams and other geological and geophysical considerations, we infer that mafic magmas from the SCN were generated by partial melting of continental lithospheric mantle in an extensional setting. Inverse modelling of primary magmas from the SCN further indicates that the source region is not depleted in high-field strength elements (HFSE) compared to large ion lithophile elements (LILE) and rare-earth elements (REE). The petrogenesis of evolved magmas from the SCN is consistent with the partial melting of the continental crust facilitated by influx of mantle-derived magmas. Generally, an extensional setting is indicated for the SCN despite continuing subduction at the Middle America Trench.